Food safety and developing markets: Research findings and research gaps - Unnevehr, Laurian J.; Ronchi, Loraine (International Food Policy Research Institute, 2014)
To better inform donor support for public food safety interventions, this paper reviews the literature on the impact of more stringent food safety standards on developing-country markets. This literature has primarily focused on the market access and economic implications of higher standards in export markets rather than on the extensive debate around market failure and public health benefits that dominates the literature in developed countries. We find that the market access benefits from compliance with public and private food safety standards are clear, as is the market exclusion that results from noncompliance. These benefits are now well documented, with more recent evidence pointing to added benefits of poverty reduction and spillovers for health and productivity.